Early transcriptomic perturbations highlight the spinal cord as a key pathogenic region in spinocerebellar ataxia type 3 - Emerson, Jacen; Nelthrope, Brianna S.; Walker, Emma A.; Mao, Grace; Shorrock, Hannah K.; McLoughlin, Hayley S. (Frontiers in Cellular Neuroscience, 2026)
Spinocerebellar ataxia type 3 (SCA3) is a neurodegenerative disease caused by polyglutamine repeat expansion in the ATXN3 gene. Despite the ubiquitous expression of ATXN3 throughout the body, SCA3 pathology is most pronounced in select, vulnerable central nervous system regions. Notably, spinal cord atrophy that is detectable by MRI emerges prior to ataxia symptom onset and progresses with disease severity. However, the pathogenic molecular signatures of the SCA3 spinal cord remain largely unexplored. Here, we present the first comprehensive analysis of the spinal cord transcriptome in SCA3 using both human and mouse model tissue. Our data reveal both early and progressive transcriptional dysregulation in the spinal cord, impacting key biological processes such as lipid metabolism, inflammation, cellular structure, and nucleic acid processing. Transcriptomic profiling of Atxn3 knockout mouse spinal cord revealed only subtle transcriptional changes with little overlap to those in SCA3 knock-in mice, indicating that spinal cord pathology arising from gene expression changes are due to mutant ATXN3 toxic gain-of-function mechanisms, rather than ATXN3 loss-of-function. In addition, we observed aberrant RNA splicing changes in KI mice, particularly in oligodendrocyte signature genes. Collectively, these novel findings position the spinal cord as a primary and early site of SCA3 pathogenesis and underscore its potential both as a sensitive regional biomarker for disease progression and as a key target for therapeutic intervention.